Piezoelectric Response of Polycrystalline Silicon‐Doped Hafnium Oxide Thin Films Determined by Rapid Temperature Cycles. (29th January 2020) - Mart, Clemens; Kämpfe, Thomas; Hoffmann, Raik; Eßlinger, Sophia; Kirbach, Sven; Kühnel, Kati; Czernohorsky, Malte; Eng, Lukas M.; Weinreich, Wenke
Abstract: The in‐plane piezoelectric response of 20 nm thick Si‐doped HfO2 is examined by exploiting thermal expansion of the substrate upon rapid temperature cycling. The sample is heated locally by a deposited metal film, and the subsequently registered pyroelectric current is found to be frequency dependent in the observed range of 5 Hz to 35 kHz. While the intrinsic response remains constant, the secondary contribution can be switched off in the high‐frequency limit due to substrate clamping. As this secondary response is generated by thermal expansion and the piezoelectric effect, this allows for extraction of the corresponding in‐plane response. By comparing pyroelectric measurements in low‐ and high‐frequency limits, a piezoelectric coefficient d 31 of −11.5 pm V −1 is obtained, which is more than five times larger than that of AlN. The magnitude of piezoelectric response increases upon electric field cycling, which is associated with a transition from antiferroelectric‐like behavior to a purely ferroelectric polarization hysteresis. The hafnium oxide material system is proposed as a promising candidate for future CMOS compatible piezoelectric micro‐ and nano‐electromechanical systems (MEMS and NEMS). Abstract : The piezoelectric in‐plane response of 20 nm thick Si‐doped HfO2 films is examined by using thermal expansion of the underlying substrate. The obtained coefficient exceeds that of AlN by a factor of 5, making doped hafnium oxide a promising candidate for future CMOS‐compatible piezoelectric micro‐ and nano‐electromechanical systems.